1996
DOI: 10.1002/bjs.1800831023
|View full text |Cite
|
Sign up to set email alerts
|

Role of the nurse endoscopist in colorectal practice

Abstract: Recent changes in the provision of colorectal services',2 have led the authors to train a nurse endoscopist in colorectal practice'. MethodsA registered general nurse was trained in flexible sigmoidoscopy and clinical coloproctology in accordance with an agreed protocol. The training took place during routine endoscopy lists in a medium-sized district general hospital. Under the direct supervision of a consultant (V.M.), the nurse (R.R.) was trained in the three main elements of colorectal endoscopy.First, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…However, in contrast to other studies [6,16,21,22] the average length of insertion in our study was much higher. A few centers in the United Kingdom have started a nurseendoscopist service, and early results from these centers are promising [6,17]. In view of the predominance achieved by left-side pathology, several centres have reported their experience with OAFS [11,13,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to other studies [6,16,21,22] the average length of insertion in our study was much higher. A few centers in the United Kingdom have started a nurseendoscopist service, and early results from these centers are promising [6,17]. In view of the predominance achieved by left-side pathology, several centres have reported their experience with OAFS [11,13,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of FS is that it is a less complicated and less risky procedure than colonoscopy and can be carried out by an appropriately trained nurse specialist. 28 It has been suggested that there is scope within the NHS to reduce the diagnostic burden for patients and endoscopy services by implementing clinical protocols which incorporate the selective use of FS, in place of WCI, for the initial investigation of patients with symptoms suggestive of distal CRC. [29][30][31][32][33] For WCI to be avoided in favour of FS, diagnostic protocols using FS for first-line investigation must be able to demonstrate INTRODUCTION NIHR Journals Library www.journalslibrary.nihr.ac.uk favourable risk-benefit profiles, in which the benefits of this less invasive procedure are balanced against the risk of a missed diagnosis of proximal cancer.…”
Section: Computerised Tomography Colonographymentioning
confidence: 99%
“…Many of the first nurse endoscopists received a more demanding and lengthy training in the procedure than existing doctor endoscopists 9 . The number of procedures required for competence, as judged by a trainer is, about the same 10 ; therefore, guidelines recommend the same training for a nurse as for a doctor-150 procedures under supervision 8 .…”
Section: Trainingmentioning
confidence: 99%
“…However, there was a possible selection bias in this study as symptomatic patients saw the doctor rather than the nurse 17 . Mashakis et al 9 found that an independent blinded assessor scored a specially trained nurse within 15% of her (doctor) trainer on various aspects of performance, with both achieving the aim of 60 cm insertion in over 70% of cases and reaching the descending colon in half, with no complications.…”
Section: Endoscopymentioning
confidence: 99%